A Case of Placenta Increta Mimicking Submucous Leiomyoma - Ali Ekiz; Ibrahim Polat; Sezcan Mumusoglu; Burchan Aydiner; Cagdas Ozdemir; Hilal Serap Arslan (Case Reports in Obstetrics and Gynecology)
In recent years with the increase in cesarean section rates, the frequency of placenta accreta cases rises. It causes 33–50% of all emergency peripartum hysterectomies. We present a 42-year-old case who was caught with early postpartum hemorrhage due to retained placental products. The ultrasonography showed a 65 × 84 mm mass in the uterine cavity after the delivery. Due to presence of early postpartum hemorrhage which needs transfusion, an intervention decision was made. The patient underwent curettage but the mass could not be removed so that placental retention was ruled out. Submucous leiomyoma was made as first-prediagnosis. Hysterectomy operation was performed as a curative treatment. Placenta increta diagnosis was made as a final diagnosis with pathological examination. As a result, placental attachment disorders may be overlooked if it is not a placenta previa case.